Model and Urgency of the Role of Academics in the CreativeIndustry Ecosystem of Malang City - Syaifudin, Yan Watequlis; Siradjuddin, Indrazno; Mundzir, Hudriyah; Fatmawati, Triana; Saputra, Pramana Yoga (PANGRIPTA, 2024)
The popularity of the creative industries continues to rise around the world, both among consumers and entrepreneurs who are due to a variety of factors, including technological advances and changes in consumer behavior. Malang City has also been recognized as one of the cities that has great creative economic potential. The direction of development of Malang City is also increasingly clear leading to strengthening its status as a creative economy city marked by three milestones. To build an optimal industrial ecosystem in the creative economy sector, especially in Malang City, requires a hexahelix synergy approach which refers to cooperation between six entities in developing a better and sustainable innovation ecosystem. Collaboration between industry and academia has a very strategic role because it can provide significant benefits for the quality of innovation and research development of the creative industry. The government also strongly encourages academics to collaborate with industry, government, media, and society, where various programs are directed to encourage collaboration between universities and industry to conduct joint research and development. A concrete example is the existence of an independent research center called ISDEI (Intelligent Systems and Digital Economic Innovation) which has collaborated for research and community service. With great academic research potential with the existence of more than 50 higher education institutions, the Association of Creative Economy Academics (AACE) is committed to being an aggregator in the creative economy ecosystem at the Malang Creative Center (MCC) that synergizes academic activities from academics with creative industry players, the Malang City government, and the creative economy community in Malang City.